Kre6 (yeast 1,6-β-transglycosylase) homolog, PhTGS, is essential for β-glucan synthesis in the haptophyte Pleurochrysis haptonemofera - Inukai, Mayuka; Kobayashi, Naoya; Endo, Hirotoshi; Asakawa, Koki; Amano, Keisuke; Yasuda, Yuki; Cenci, Ugo; Colleoni, Christophe; Ball, Steven; Fujiwara, Shoko (Frontiers in Bioengineering and Biotechnology, 2023)
Haptophytes synthesize unique β-glucans containing more β-1,6-linkages than β-1,3 linkages, as a storage polysaccharide. To understand the mechanism of the synthesis, we investigated the roles of Kre6 (yeast 1,6-β-transglycosylase) homologs, PhTGS, in the haptophyte Pleurochrysis haptonemofera. RNAi of PhTGS repressed β-glucan accumulation and simultaneously induced lipid production, suggesting that PhTGS is involved in β-glucan synthesis and that the knockdown leads to the alteration of the carbon metabolic flow. PhTGS was expressed more in light, where β-glucan was actively produced by photosynthesis, than in the dark. The crude extract of E. coli expressing PhKre6 demonstrated its activity to incorporate 14C-UDP-glucose into β-glucan of P. haptonemofera. These findings suggest that PhTGS functions in storage β-glucan synthesis specifically in light, probably by producing the β-1,6-branch.